Évolution de l’économie canadienne - Parenteau, Roland (Assurances)

(untitled) (HEC Montréal, 1982)
In his article, Mr. Parenteau presents his view of the economic situation over the past fifty years, a time span equalling the existence of Assurances. We should like to thank him for having reviewed the economic trends and the principal elements having prevailed throughout this period. His reflections allow him to draw the following conclusion: the Canadian economy has made great strides in the last fifty years but is currently plagued by a profound malaise. To counter this situation, the author advises we rid ourselves of a number of preconceived views and most importantly, channel a greater flow of energy and ideas into improving productivity and restoring economic harmony.